In vitro antiplasmodial properties of selected plants of Sabah - Shaari, Khozirah; Abdullah, Noor Rain; Mohd Janib, Siti Najila; Imiyabir, Zamrie; Madani, L.; Chomel, Rohaya; Mohamad, Rosilawati; Hashim, Nuziah; Goh, S. H.; Ismail, Zakiah (Universiti Putra Malaysia Press, 2011)
The antiplasmodial activity of the crude extracts of thirty plant species collected from Sabah was evaluated using chloroquine-sensitive strain (D10) and chloroquine-resistant strain (Gombak A) of Plasmodium falciparum. Significant activities were observed for the bark extract of Polyalthia insignis (IC50 3.89 and 11.89 µg/ml against Gombak A and D10, respectively), the leaf extracts of Kopsia dasyrachis (4.62 µg/ml against Gombak A) and Litsea elliptibacea (IC50 8.88 µg/ml against Gombak A), as well as the leaf and bark extracts of Neouvaria acuminatissima (IC50 6.90-10.08 and 0.69 µg/ml against Gombak A and D10, respectively), and the bark extract of Polyalthia microtus (IC50 9.0 and 12.12 µg/ml against Gombak A and D10, respectively).